GENDER GAP IN SCIENCE, TECHNOLOGY AND MATHEMATICS (STM) EDUCATION: IMPLICATIONS TO ENTREPRENEURIAL SKILLS DEVELOPMENT - Auwal, Yusha'u Muhd; Umar, Shehu (Sokoto Educational Review, 2020)
Gender differentials in schools, workplaces and business still exist in Nigeria. Girls and women remain substantially under-represented in Science, Technology and Mathematics (STM) education. Although the problem is recognized, but its implication is under estimated. Tins paper reviews the existing gender gap in Science, Technology and Mathematics (STM) education. The paper also examined the implications of gender gap to entrepreneurial skills development. Finally, we share the same believe with (Wasagu & Muhammed, 2007:88) who believed that “today more than ever before, females need to be provided with access quality, Technology and Mathematics Education.” Suggestions were offered on how to close the gender gap in STM education that will lead us to a viable, qualitative entrepreneurial skills development that could be free from gender bias.